P11.15.B First multicentric real-life experience with the combination of lomustine and temozolomide in newly diagnosedMGMT promoter methylatedIDH wildtype glioblastoma. (5th September 2022) - Lazaridis, L; Schmidt, T; Agkatsev, S; Blau, T; Spille, D; Heider, S; Schulz, T; Bumes, E; Oster, C; Feldheim, J; Stummer, W; Kessler, A; et al.
Abstract: Background: The CeTeG/NOA-09 trial assessed in a randomized phase 3 setting, whether combined treatment of lomustine together with temozolomide was superior to temozolomide treatment alone in newly diagnosed MGMT (O(6)-methylguanine-DNA-methyltransferase) promoter methylated glioblastoma patients. Survival was significantly improved from 31.4 months with temozolomide alone to 48.1 months with the combination of lomustine plus temozolomide. In view of this encouraging data - suggesting this combination could have a significant impact on the survival of newly diagnosed glioblastoma patients - we were curious to assess safety and efficacy of this regimen under real-life conditions. Material and Methods: We collected clinical and radiographic data from adult newly diagnosed MGMT promoter methylated IDH (isocitrate dehydrogenase) wildtype glioblastoma patients treated at five neuro-oncology centers in Germany. As a requirement for inclusion, first-line treatment with lomustine plus temozolomide had to be performed for at least six weeks (one course). The available radiographic data was independently reviewed by an experienced board-certified neuro-radiologist. Results: In total, 70 patients were included. Median progression-free survival of the full cohort was 14.4 months and median overall survival was 36.0 months. Patients who received TTFields (Tumor Treating Fields) treatment for eight weeks or longer together with the combination of lomustine plus temozolomide ( n =22, 31%) had a prolonged progression-free survival compared to those patients who received TTFields treatment less than eight weeks or did not receive treatment with TTFields ( n =48, 69%) (21.5 months versus 11.2 months; HR: 2.118, 95% CI: 1.245-3.605; p =0.0105). In a multivariable Cox regression analysis the use of TTFields for eight weeks or longer together with the combination of lomustine plus temozolomide as well as the application of at least five courses of CeTeG therapy emerged as independent prognostic factors for progression-free survival and overall survival. Pseudoprogression occurred in n =16 (33%) of the patients. We observed no treatment related deaths and high-grade hematotoxicity in n =31 (44%) of the patients. Conclusion: The results from this multicentric trial that investigated newly diagnosed MGMT promoter methylated IDH wildtype glioblastoma under real-life conditions indicate toxicity and survival estimates comparable to the CeTeG/NOA-09 trial. The use of TTFields for at least eight weeks in combination with this regimen was independently associated with extended progression-free and overall survival.